Panton-Valentine Leukocidin-Positive Staphylococcus aureus: a successful infectious enemy? - Syahirah Samsudin; Hassanain Al-Talib; Zaini Mohd Zain; Chandrika Murugaiah (Japan Health Sciences University & Japan International Cultural Exchange Foundation, 2020)
Objective: To highlight the current knowledge on pathogenicity, mode of transmission and emergence of antimicrobial resistance in panton-valentine leukocidin (PVL)-positive Staphylococcus aureus. Material and Methods: Previously published abstracts and full articles relating to the study topic were selected, and relevant articles were downloaded and reviewed. Manuscripts which covered PVL and S. aureus were chosen for structured review. Quality assessment checks were performed on the papers and the findings were compared and interpreted. Results: Recent reports have shown a worldwide increase in S. aureus infections caused by PVL-positive organisms. Moreover, PVL-positive S. aureus is responsible for more than one-third of all community and hospital based infections, associated with high mortality and morbidity. Nasal carriage transmission of PVL-positive S. aureus is an important risk factor for staphylococcal infections, with the primary source of infection in hospitals coming from colonized patients and healthcare workers. Conclusions: Increased diagnostic and management surveillance of suspected and confirmed staphylococcal infections will help decrease PVL-positive S. aureus spread. Indiscriminate antibiotics use must be strictly controlled in healthcare settings and communities to prevent further resistance selection by microorganisms. It is therefore crucial to initiate a global enhancement in the surveillance of PVL-positive S. aureus, to control the spread of infection.